Perencanaan Pengembangan Kawasan Pariwisata Pantai Lebih, Desa Lebih, Kabupaten Gianyar - Ariani, Ni Ketut Desi; Suryawan, Ida Bagus (JURNAL DESTINASI PARIWISATA; Vol 6 No 2 (2018): VOL 6, NO 2 (2018): (JULY - DECEMBER) JURNAL DESTINASI PARIWISATA, 2019)
Lebih beach tourism area is a coastal protection areas in Gianyar Subdistrict. The main problem is the abrasion that occurs along the coastline and damage the naturalness of the beach. Therefore, Gianyar regency government set more coastal tourism area as a priority  and certain area , that must be maintained and preserved its existence as a tourism area in Bali. This study aims to determine the planning of tourism area in Lebih Beach to development the  priority coast of the tourism area , so it can be worth visiting both in the form of physical and non physical assistance. This research is important to do because the destruction of this coastal environment will determine the sustainability of tourism in Lebih Beach. The research methodology used in this research is mix method , with data source in the form of secondary and primary data. The data collection techniques used in the form  are observation, interviews and qualitative documents. After collecting process, the data analyzed descriptively. The results show that planning for development of the area in Lebih Beach requires several thing, such as direction of the function area, spatial direction, facilities and utilities plan, transportatation plan, indication of priority area program, and activity development plan. Therefore, the participant of every stakeholder is needed for the development planning tourism area to success. Keywords: Planning, Tourism Area, Lebih Beach